Telemonitoring is acceptable amongst community dwelling older Australians with chronic conditions. Issue 4 (December 2016) - Halcomb, Elizabeth; Purcell, Renee; Hickman, Louise; Smyth, Elizabeth
Summary: Background: Telemonitoring is an innovative model of care being implemented to address the growing burden of chronic and complex disease. Objectives: This paper explores the perceptions of community dwelling older people with chronic and complex conditions towards a general practice nurse-led telemonitoring intervention. Method: A pre-test post-test intervention study was conducted with consumer surveys administered before and after the intervention. The telemonitoring intervention consisted of a period of home monitoring during which daily vital signs and symptoms were transmitted to the general practice nurse. Results: 21 participants completed both pre and post-test surveys. There was a significant difference between pre and post ratings on the survey item "the use of telemonitoring equipment seems difficult to me" ( p = 0.013 ), and "telemonitoring will be a standard way of health care delivery in the future" ( p = 0.032 ) . Approximately half of the participants reported that telemonitoring provided them with a sense of security and peace of mind, assisted them to manage their health, in addition to improving their confidence in managing their care. Most participants felt more involved and expressed that daily monitoring helped them to understand changes in their condition. Conclusion: Telemonitoring is acceptable to Australian community dwelling older persons with chronic conditions. Prior experience with computers and technology may not be a meditating factor in acceptability. The use of telemonitoring not only provided important physiological information to health professionals but also has the potential to empower older people by allowing them to better understand their own health.